2023
DOI: 10.1055/a-2070-1767
|View full text |Cite
|
Sign up to set email alerts
|

Lone Pair Participation in a Decarboxylation Reaction: A New Design of a Boradecarboxylation Reaction

Abstract: For the mechanism of decarboxylation reactions, all textbooks show electrons moving from the πC=O bond. However, the most electron-donating bond orbital in the carbonyl group is expected to be the lone pair(s) on the oxygen. Thus, orbital theory with delocalization from a lone pair may be more appropriate than delocalization from the πC=O orbital. We confirmed our idea by theoretical calculations. In the TS, if we use 2-substituted

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…___________________________________________________ Recently, we demonstrated that orbital theory, where the lone pair on the oxygen plays a role, is more appropriate for describing the decarboxylation reaction than the electronic theory, which is mentioned in almost all textbooks, where an arrow showing movement of the electron is drawn from C=O (Figure 2). 3 Here, we investigate the reaction mechanism in detail from the perspective of bond interaction.…”
mentioning
confidence: 99%
“…___________________________________________________ Recently, we demonstrated that orbital theory, where the lone pair on the oxygen plays a role, is more appropriate for describing the decarboxylation reaction than the electronic theory, which is mentioned in almost all textbooks, where an arrow showing movement of the electron is drawn from C=O (Figure 2). 3 Here, we investigate the reaction mechanism in detail from the perspective of bond interaction.…”
mentioning
confidence: 99%